Gamification in Digital HR System: A Systematic Literature Review of Trends, Game Elements, and Audiences - Cahyo Prianto; Al Novianti Ramadhani Sulaksono (Dinasti Publisher, 2025)
This study presents a Systematic Literature Review (SLR) on the application of gamification in recruitment and job training. Using the PRISMA method and a literature management platform for automated filtering and thematic grouping, 41 Scopus-indexed studies published between 2020 and 2025 were analyzed. The findings show a steady increase in research activity, with notable peaks in 2020 and 2024, and most studies originating from the United States and Europe. Points, Badges, and Leaderboards (PBL) remain the most frequently applied game elements, often combined with feedback, avatars, narrative components, challenges, and progress bars to enhance engagement and learning outcomes. Gamified e-learning platforms were the most common form of implementation, followed by serious games, mobile applications, and generic HR dashboards. Most studies (85.4%) targeted existing employees, while only 7.3% focused on recruitment, indicating a significant opportunity for broader application in this area. As a key contribution, this study proposes a three-dimensional taxonomy of gamification in HR systems, categorized by platform type, game element depth, and user segmentation. This taxonomy provides a structured framework for aligning gamification strategies with organizational objectives and user profiles. The review also identifies an emerging shift toward personalized and narrative-driven gamification designs, moving beyond conventional PBL-focused approaches.